Optical detection of different phenolic compounds by means of a novel biosensor based on sol–gel immobilized laccase. (29th May 2017) - Lepore, Maria; Portaccio, Marianna
Abstract: A novel sol–gel‐based biosensor exploiting the optical absorption properties of sol–gel immobilized laccase has been constructed to increase enzyme specificity toward different phenolic substrates. Laccase from Trametes versicolor has been immobilized in optically transparent sol–gel matrices. Using Fourier transform infrared spectroscopy and data analysis based on a wavelet algorithm, a successful enzyme immobilization has been determined. The changes in the optical absorption spectra of laccase reaction products at 425, 375, and 400 nm have been used to determine hydroquinone, resorcinol, and catechol concentrations, respectively. Owing to the slow response time of the hydroquinone–laccase reaction, our optical biosensor has been tested with resorcinol and catechol. Linear ranges up to 1.4 and 0.2 mM, limit‐of‐detection (LOD) of 4.5 and 0.6 μΜ, have been evidenced for resorcinol and catechol, respectively. Data for determining the resorcinol concentration have been particularly interesting since no other biosensor device has been reported in the literature. In comparison with other biosensors using laccase from the same native source, our biosensor has been characterized by larger linear ranges, significant sensitivities, and good LODs. To challenge our biosensor with real samples, tap water samples spiked with known amount of catechol and resorcinol have been employed.